Rotten Spouses, Family Transfers and Public Goods - Helmuth Cremer; Kerstin Roeder (Institute for the Study of Labor (IZA), 2014)
We show that once interfamily exchanges are considered, Becker's rotten kids mechanism has some remarkable implications that have gone hitherto unnoticed. Specifically, we establish that Cornes and Silva's (1999) result of efficiency in the contribution game amongst siblings extends to a setting where the contributors (spouses) belong to different families. More strikingly still, the mechanism does not just have consequences for efficiency but it may have dramatic redistributive implications. In particular, we show that the rotten kids mechanism combined with a contribution game to a household public good may lead to an astonishing equalization of consumptions between the spouses and their parents, even when their parents' wealth levels differ. We consider two families, each consisting of a parent and an adult child, who are linked by the young spouses. Children contribute part of their time to a household (couple) public good and provide attention to their respective parents in exchange for a bequest. Spouses behave towards their respective parents like Becker's rotten kids; they are purely selfish and anticipate that their altruistic parents will leave them a bequest. The most striking results obtain when wages are equal and when parents' initial wealth levels are not too different. For very large wealth differences the mechanism must be supplemented by a (mandatory) transfer that brings them back into the relevant range. When wages differ but are similar the outcome will be near efficient (and near egalitarian).
Keywords: D13; D61; D64; 330; rotten kids; altruism; private provision of public good; subgame perfect equilibrium; family aid